Carbon input and allocation by rice into paddy soils: A review. (June 2019) - Liu, Yalong; Ge, Tida; Zhu, Zhenke; Liu, Shoulong; Luo, Yu; Li, Yong; Wang, Ping; Gavrichkova, Olga; Xu, Xingliang; Wang, Jingkuan; Wu, Jinshui; Guggenberger, Georg; et al.
Abstract: Knowledge of belowground C input by rice plants and its fate is essential for managing C cycling and sequestration in paddy soils. Previous reviews have summarized C input and the pathways of root-derived C in upland soils by labeling with 14 C or 13 C ( 13/14 C), while rice rhizodeposition and C input in paddy soils have not been comprehensively evaluated. Here, we analyzed the results of 13/14 C pulse and continuous labeling studies using 112 datasets from 13 articles on the allocation and pathways of photosynthesized C by rice plants to assess C input, budget, and amount stabilized in paddy soils. Overall, 13/14 C partitioning estimated by continuous labeling was 72% to the shoots, 17% to the roots, 10% to the soil, and 1.3% was recovered in microbial biomass. Pulse-labeling studies showed a similar C partitioning: 79%, 13%, 5.5%, and 2.1%, respectively. The total belowground C input estimated based on continuous labeling was 1.6 Mg ha −1 after one rice season, of which rhizodeposition accounted for 0.4 Mg C ha −1 . Carbon input assessed by pulse labeling was slightly lower (total belowground C input, 1.4 Mg ha −1 ; rhizodeposition, 0.3 Mg C ha −1 ; 14 days after labeling). Rice C input after one cropping season was lower than that by upland plants (cereals and grasses, 1.5–2.2 Mg ha −1 ). In contrast to upland crops, most paddy systems are located in the subtropics and tropics and have two or three cropping seasons per year. We conclude that (1) pulse labeling underestimates the total belowground C input by 15%, compared with that by continuous labeling, and (2) rhizodeposition of rice accounts for approximately 26% of the total belowground C input, regardless of the labeling method used. Based on allocation ratios, we suggest a simple and practical approach for assessment of the gross C input by rice into the soil, for partitioning among pools and for long-term C stabilization in paddies. Graphical abstract: Image 1 Highlights: We reviewed the amount of C input by rice plants into paddy soils based on 13 C or 14 C labelling studies. Pulse labeling underestimated the total belowground C input by 15% compared with continuous labeling. Rhizodeposition accounted for approximately 26% of the total belowground C input by rice. Simple method was proposed for the raw assessment of C input into the soil.